(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2018)
Rethinking the concept of citizenship means understanding the historical nature of the relationship between citizenship and nation-state and going beyond the definition of a formal and legal status, such as the membership to a political system. In the global era, citizenship undergoes a process of deterritorialization that produces a fragmentation and multiplication of forms, figures and experiences. The text aims at illustrating that citizenship is a field of tensions: it is crossed by the struggles, specially concerning the violation of its borders, of individuals who are excluded or includedin a differentiated or subordinate way. These “acts of citizenship” are acts through which individuals become, make themselves citizens. At the same time, interpreting citizenship not only as a formal status, but as a space of conflict and movement, based on the extension of rights, does not mean denying its normative dimension: citizenship emerges between normative and processual dimension. Citizenship is a project in continuous construction and reconstruction, producing the possibility of access to rights. When considered as a process of political subjectivation, citizenship is a dynamic, ever-changing institution. Today, in particular, cities are the crucial space of new emerging forms of citizenship.